Менты. Выстрел из прошлого: [повести] / А. Иванов, Д. Рубин - Иванов Андрей Юрьевич (АСТ, 2002)
Экземпляры: ф.2 (2003) / Инвентарный номер: 47547 / Цена: / Сис.шифр: 84(2Рос=Рус)6-4 / Авт.знак: И 20 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6-44